THE RELATIONSHIP BETWEEN EQ (EMOTIONAL QUOTIENT) AND SQ (SPIRITUAL QUOTIENT) WITH LEARNING MOTIVATION IN ISLAM RELIGIOUS EDUCATION IN STUDENTS AT SMA NEGERI 20 MAKASSAR (International Conference on Social and Islamic Studies, 2022)
This study aims to describe 1) EQ (Emotional Quotient) of students in class XI IPS SMAN 20 Makassar, 2) SQ (Spiritual Quotient) of students in class XI IPS SMAN 20 Makassar, 3) Motivation to study Islamic Religious Education in class XI IPS SMAN 20 Macassar. This study aims to examine: 1) The relationship between EQ (Emotional Quotient) and the motivation to study Islamic Religious Education in class XI IPS students at SMAN 20 Makassar, 2) The relationship between SQ (Spiritual Quotient) and the motivation to study Islamic Religious Education in class XI IPS SMAN 20 Makassar, 3) The relationship between EQ (Emotional Quotient) and SQ (Spiritual Quotient) of students in class XI IPS SMAN 20 Makassar, 4) The relationship between EQ (Emotional Quotient) together with SQ (Spiritual Quotient) and motivation to study Religious Education Islamic students of class XI IPS SMAN 20 Makassar. This research uses a quantitative approach with the type of ex post facto research. The population in this study were all students of class XI IPS SMAN 20 Makassar, totaling 60 students. Sampling using a population sample of 60 students of class XI IPS SMAN 20 Makassar. The research instrument uses the EQ (Emotional Quotient) scale, SQ (Spiritual Quotient) and learning motivation scale. Data analysis techniques using descriptive statistical analysis and inferential statistics, namely product moment correlation and multiple correlation analysis techniques. Based on the results of the descriptive analysis, it was obtained: (1) the score of the students' EQ (Emotional Quotient) category was 71.7% in the medium category. (2) the students' SQ (Spiritual Quotient) category score is 71.7% in the medium category. (3) the score of students' Islamic Religious Education learning motivation category is 61.7% in the medium category. Based on the results of inferential analysis obtained: (1) There is a relationship between EQ (Emotional Quotient) and motivation to learn Islamic Religious Education. This is based on the results of the sig test. FChange = 0.653 <0.05. (2) There is a relationship between SQ (Spiritual Quotient) and motivation to study Islamic Religious Education. This is based on the results of the sig test. F Change = 0.694 <0.05. (3) There is a relationship between EQ (Emotional Quotient) and SQ (Spiritual Quotient). This is based on the results of the sig test. F Change = 0.742 <0.05. (4) There is a relationship between EQ (Emotional Quotient) and SQ (Spiritual Quotient) with the motivation to study Islamic Religious Education. This is based on the results of the sig test. F Change = 0.742 <0.05. So it can be concluded that H0 is rejected, which means that there is a positive and significant relationship between EQ (Emotional Quotient) and SQ (Spiritual Quotient) with the motivation to study Islamic religious education for students in class XI IPS SMAN 20 Makassar.